URGENT ISSUES OF LAW IN INTERACTION BETWEEN DENTAL SERVICE AND STAKEHOLDERS OF HEALTHCARE ORGANIZATION - Всеволод Владимирович Кан; Алямовский Василий Викторович; Капитонов Владимир Федорович; Лазаренко Анна Валерьевна (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2013)
This article describes the main innovations, as well as possible ways to improve the organization of medical care in the Russian Federation, in particular, dental care. The article considers legal and regulatory acts, laws and orders regulating the process of providing medical assistance to the population of the Russian Federation. The main problems and shortcomings in the organization of dental care - are the lack of programs for prevention of dental disease, the lack of standards and protocols for the treatment of patients, the lack of qualification characteristics of dentists.DOI:  http://dx.doi.org/10.12731/2218-7405-2013-5-6